Synthesis, characterization and biological analysis of the complex [VO(Hdhp)(2)] (H(2)dhp=2,3-dihydroxypyridine) - Pepato, Maria Teresa [UNESP]; Alberconi, Mayara F. [UNESP]; da Rocha, Michelle C. [UNESP]; Vendramini, Regina Célia [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Batista, Alzir A.; de Souza, Elizeu J.; Garcia, Edgardo; Deflon, Victor M. (Springer, 2008)
A new vanadium (IV) complex with the monoanion of 2,3-dihydroxypyridine (H(2)dhp), or 3-hydroxy-2(1H)-pyridone, was synthesized, characterized by physicochemical techniques and tested biologically. The EPR data for the [VO(Hdhp)(2)] complex in DMF are: g(x) = 1.9768, g(y) = 1.9768 and g(z) = 1.9390; A values (10(-4) cm(-1)): A(x), 59.4; A(y//), 59.4; A(z), 171.0. The vV=O band in the IR spectrum of the complex is at 986 cm(-1). The complex is paramagnetic, with mu(eff) = 1.65 BM (d(1), spin-only) at 25 degrees C. The irreversible oxidation process [V(V)/V(IV)] of the [VO(Hdhp)(2)] complex, as revealed in a cyclic voltammogram, occurs at 876 mV. The calculated molecular structure of [VO(Hdhp)(2)] shows the vanadium(IV) center in a distorted square pyramidal environment, with the oxo ligand in the apical position and the oxygen donor atoms of the Hdhp ligands in the basal positions. The ability of [VO(Hdhp)(2)] to mimic insulin, and its toxicity to hepato-biliary functions, were investigated in streptozotocin-induced diabetic rats and it was concluded that the length of treatment and the amount of [VO(Hdhp)(2)] administered were effective in reducing experimental diabetes.